Variety-specific selenium accumulation patterns and quality attributes of rice following foliar selenium application - Fanbin Meng; Jing Wang; Donghai Wang; Jianfei Wang (PLoS ONE, 2025)
In the context of addressing regional selenium (Se) deficiencies in China, this study undertook an investigation into the efficacy of foliar Se spray on 12 rice varieties. The primary focus was on assessing rice quality and Se enrichment in various plant components, namely grain, roots, stems, and leaves. The foliar Se spray led to an increase in soil Se content from 0.13 to 0.26 mg. Growth promotion was observed, with rice variety ZLY experiencing a height increase of 19.10 cm, while variety QYX had only a 0.90 cm increase. However, grain weight and numbers were minimally affected. Foliar Se spray had different impacts on rice quality among varieties and treatments. Specifically, variety TLY consistently had the highest numbers of brown and milled rice grains, whereas TXJ and LY had the lowest numbers of brown and milled rice grains respectively. Foliar Se spray had diverse effects on protein contents, resulting in the highest glutelin content of more than 4% and prolamin content as low as less than 0.1%, while the total protein content remained largely unchanged. Moreover, rice varieties demonstrated varying Se enrichment capacities, with the highest for varieties ZLY and QYX grain, and the lowest for LY, TXJ, and JLY grain. The results offered technical support for the selection and promotion of selenium-enriched rice, thereby presenting a potential solution to Se deficiency in China.